FACTORS ASSOCIATED WITH THE SEVERITY OF FINDINGS ON HEPATIC TRANSIENT ELASTOGRAPHY AMONG PERSONS WITH TYPE 2 DIABETES AND FATTY LIVER - Fernando, Joseph Noel; Lim-Alba, Rebecca; Alba, Willy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE This study aims to determine the relationship between the different factors associated with the severity of Fibroscan with CAP findings among patients with type 2 diabetes and fatty liver. METHODOLOGY This is a cross-sectional study. Seven hundred four Fibroscan with Controlled Attenuation Parameter (CAP) results were electronically retrieved from a diagnostic center. 285 charts of diabetic patients with fatty liver on ultrasound were reviewed. One hundred sixty-four patients with fatty liver on ultrasound and Fibroscan with CAP were included in the study. Several factors were analysed in relation to the severity of Fibroscan with CAP findings in the study group. RESULTS 55.5% (91/164) had significant fibrosis and cirrhosis. Hepatic steatosis prevalence was 96% (158/164). Diabetes >5 years (OR 1.75), HbA1c ≥7% (OR 2.25) and high SGPT levels (OR 2.39) were associated with liver fibrosis and cirrhosis. BMI >25 kg/m2 (OR 1.45), triglyceride levels >150 mg/dl (OR 1.31) and HbA1c ≥7% (OR 1.74) were associated with hepatic steatosis. CONCLUSION Factors associated with the severity of hepatic fibrosis, cirrhosis and steatosis included above normal BMI, disease duration of >/= 5 years, poor glycemic control andelevated levels of ALT, and serum triglycerides.